PENGABDIAN MASYARAKAT DENGAN TEMA PENGELOLAAN MANAJEMEN SUMBER DAYA MANUSIA (MSDM) PADA UKM SANGKAR BURUNG DI KELURAHAN BANYUANYAR KECAMATAN BANJARSARI KOTA SURAKARTA - Rahayu Triastity (Lembaga Penelitian dan Pengabdian Masyarakat, 2018)
Community Services Program aims in order so that SME have the ability to Community services program aims in order so that SMES have the entrepreneurial spirit so that there is continuity of effort, which could ultimately increase revenue. Target audience this community service activities is SME Birdcage in Village of Banyuanyar sub-district of Banjarsari town of Surakarta. Extension methods include lectures, discussions, question and answer. Activity plan extension done 2 times, the first meeting of a talk foster entrepreneurial soul, second meeting: improving the skills of the production. The outer of this activity are: 1) the SME has the spirit of entrepreneurship. 2) SME have the skills to make bird cage. The transfer of science and technology held it aims so that SME have a spirit of entrepreneurship and have skills in making bird cage.Key words: entrepreneurial spirit, production skills, SME